Mendalami Konsepsi Ketuhanan dan Jiwa dalam Kitab Itihasa - I Made Putra Aryana; Putu Eddy Purnomo Arta; Ni Kadek Supadmini; Kadek Jayanthi Riva Prathiwi (Sphatika: Jurnal Teologi, 2021)
This article aims to find out the basics of Hindu teachings contained in the book Itihasa. The Hindu teachings include the concept of divinity and the concept of the soul, because in Itihasa these teachings are implicit in the behavior of everyday life. This article is written using the library method and in-depth study of the literature.Itihāsa is Hindu literature that tells the story of the heroism of Hindu knights in the past and is peppered with religious philosophies, mythology, and supernatural beings. Itihasa means this has happened so.Itihasa consists of two epics, namely Ramayana which consists of seven parts and Mahabarata which consists of 18 parts. The concept of Divinity in the Ramayana book mentions many gods, but is categorized as monotysm because they believe in one God who is supreme among all the god. Divinity in the Mahabharata is closely related to Divine knowledge in the Upanisad, Pancasikha, Samkya, Yoga, Pancaratra, Vaisesika, and Vedanta. Jiwa or Atman in Itihasa is the deepest manifestation of each person.The soul is causeless and unchanging.